THE IMPORTANCE OF ATHLETICS FOR STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Ochilov Elbek Olimovich (Journals Park Publishing, 2023)
The article describes the methodology of conducting athletics classes in higher educational institutions, the importance and role of athletics for the body of students. The place of athletics in the system of physical education, the methods of performing exercises are peculiar only to athletics, the place of athletics among other sports.
Keywords: Athletics, methodology, physical education, sports, running exercises, types of athletics.